Advances in Preterm Delivery - Sheiner, Eyal (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Preterm delivery (PTD; < 37 weeks' gestation) complicates 5%-13% of deliveries worldwide, depending on the geographical and demographical characteristics of the population tested. It is the leading cause of perinatal morbidity and mortality, as well as maternal morbidity. In fact, prematurity has both short- and long-term consequences for affected offspring and can leave these individuals with lifelong disabilities, even after the available interventions are attempted. While various risk factors for preterm birth are well-recognized, the etiology for preterm birth is multifactorial. Preterm parturition is a syndrome resulting from the premature activation of the common pathway of parturition, including an increased myometrial contractility; cervical ripening/dilatation and effacement; and membrane/decidual activation. Because the prevalence of preterm birth is so high, it is thought to put more financial, medical, and emotional stress on affected communities than any other perinatal issue. In past years, most of the research interest resulted in the prevention of preterm birth in order to alleviate the complications of prematurity. However, recent evidence suggests that the effect of preterm birth goes beyond the impact on the future health of both the mother and her offspring as well as the specific delivery in which preterm delivery has occurred. This book focuses on the risk factors, perinatal outcomes, and long-term consequences of this critical problem.